MOBILE APP DESIGN FUNCTIONALITY WITH DIGITALIZED CULTURAL HERITAGE OBJECTS OF KHARKIV CITY AND KHARKIV REGION - Bedrina, Nadiia (Ukrainian Cultural Studies, 2023)
The topic of recovery after the consequences of a full-scale invasion is currently very relevant. The digitization of cultural heritage objects has significant potential for the promotion of Ukrainian culture both within the country and beyond. This contributes to the preservation and study of history and cultural traditions, and also attracts the attention of tourists and researchers who want to learn more about the rich cultural heritage of Ukraine. The introduction of innovative approaches to the post-conflict recovery process is one of the ways to overcome the cultural crisis. Digitized cultural heritage objects are valuable information resources that enable preservation, research and promotion of cultural heritage. The purpose of the article is to outline the possibilities and prospects of creating mobile applications for the preservation of the cultural heritage of Ukraine on the example of the Kharkiv region. The research methodology is based on general scientific methods of analysis and synthesis. The phenomenological approach made it possible to investigate mobile applications as a phenomenon of modern culture. An axiological approach allows considering the valuable status of cultural heritage objects in Kharkiv and the region.Scientific novelty and practical significance: based on the material of previous projects related to the design of mobile applications and the digitization of Kharkiv's cultural heritage objects, further vectors of work have been determined. Conclusions: thus, in this study, we considered the possibilities and prospects of creating the functionality of mobile applications using digitized 3D objects for the preservation of the cultural heritage of Ukraine on the example of the Kharkiv region. The research highlighted functionality in the design of mobile applications with digitized 3D cultural objects: augmented reality (AR), social interaction, navigation, historical context, multimedia, gamification, interactivity, virtual tours and museums, personalization, accessibility.
Keywords: mobile app design; digitization of cultural heritage objects; Kharkiv culture; application functionality